2019
DOI: 10.1016/j.respol.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Human capital and innovation: the importance of the optimal organizational task structure

Abstract: Management literature has identified high-skilled human capital as a crucial dimension of innovation processes at the firm level. In this study, we introduce an alternative view of human capital based on the tasks that firms' workers perform. We propose a measure of cognitive analytical and interpersonal tasks: the degree of abstractism.We argue that the level of abstractism of a firm has an effect on a firm's propensity to innovate and on its product innovation performance. We hypothesize that while the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 88 publications
(148 reference statements)
1
68
1
5
Order By: Relevance
“…Concerning the indirect effect of human capital on export diversification through the innovation channel, Sun et al (2020) have relied on China's firm-level data, and shown that highly educated human capital stock exerts a strong positive effect on the probability and the quantity of firm innovation. The importance of human capital accumulation for innovation has also been emphasized by authors such as Fonseca et al (2019), while that of innovation for export product diversification has been stressed by Chen (2013).…”
Section: Effect Of Human Capital On Economic Growth Volatilitymentioning
confidence: 99%
“…Concerning the indirect effect of human capital on export diversification through the innovation channel, Sun et al (2020) have relied on China's firm-level data, and shown that highly educated human capital stock exerts a strong positive effect on the probability and the quantity of firm innovation. The importance of human capital accumulation for innovation has also been emphasized by authors such as Fonseca et al (2019), while that of innovation for export product diversification has been stressed by Chen (2013).…”
Section: Effect Of Human Capital On Economic Growth Volatilitymentioning
confidence: 99%
“…Fourth, a wide literature has insisted that organizational structure influences R&D (Chen, Huang, & Lin, 2012; Petroni, Venturini, & Verbano, 2012; Zhang & Baden‐Fuller, 2010) and human capital (Daghfous, 2004; Fonseca, de Faria, & Lima, 2019; Kianto, Sáenz, & Aramburu, 2017). Thus, popular proxies for absorptive capacity such as R&D and human capital may relate implicitly or rather directly to organizational innovation.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Innovation dynamics which are key determinants of sustainable growth for countries and firms are influenced by a number of factors including human capital, knowledge creation and diffusion. Human capital which is defined as individual's knowledge, skills, expertise, and abilities that allow for changes in action and economic growth (Coleman, 1988;Fonseca et al, 2019) is a critical ingredient for innovation to occur. Rosenberg (1972) noted that human capital is an essential prerequisite for the use and effective exploitation of innovative technology (Asongu and Nwachukwu, 2018).…”
Section: Innovation and Inclusive Developmentmentioning
confidence: 99%